Tonsil microbiocenosis and salivary lactate dehydrogenase activity in children with infectious mononucleosis - Kh.P. Klymenko (Aktualʹnaâ Infektologiâ, 2021)
The article analyzes clinical data, blood test results, tonsil mucus bacteriological testing, and salivary lactate dehydrogenase activity in children with acute infectious mononucleosis caused by an Epstein-Barr viral infection. Research involves 280 children aged from 7 months to 19 years 8 months with infectious mononucleosis, who were hospitalized in the Lviv Infectious Clinical Hospital. Group 1 included 234 children infectious mononucleosis caused by Epstein-Barr virus, group 2 — 46 patients with infectious mononucleosis caused by the combination of Epstein-Barr virus and cytomegalovirus. Severe hepatosplenomegaly, lymphadenitis, nasal speech and snoring, hyperthermic syndrome, acute tonsillitis were found in patients with infectious mononucleosis. A bacteriological study identified a number of pathogens that can be classified as pathogenic or opportunistic flora. Staphylococcus aureus, Streptococcus pneumoniae, Pseudomonas aeruginosa, Candida fungi were identified in 43.8 % of children with an isolated form of mononucleosis and in 51.7 % of children with mixed infection. In children with infectious mononucleosis caused by mixed infection, we observed the more severe course of the disease and a significantly higher lactate dehydrogenase activity. A significantly increased activity of lactate dehydrogenase in the saliva of patients with infectious mononucleosis in the presence of pathogenic microflora on the mucous membranes indicates destructive processes in the tissues of the tonsils.